Fe-doped tricalcium phosphates: crystal structure and degradation behavior. (16th December 2020) - Yoo, Kyung-Hyeon; Kim, Hyeonjin; Sun, Woo Gyeong; Kim, Yong-Il; Yoon, Seog-Young
Abstract: β -tricalcium phosphate ( β -TCP, Ca3(PO4)2) is biodegradable ceramics with chemical and mineral compositions similar to those of bone. It is a potential candidate for bone repair surgery, and substituting the Fe ions can improve its biological behavior. In this study, we investigated the effect of Fe ions on the structural deviation and in vitro behavior of β -TCP. Fe-doped β -TCP were synthesized by the co-precipitation method, and the heat treatment temperature was set at 1100 °C. The chemical state of the Fe-doped β -TCP was analyzed by x-ray photoelectron spectroscopy, while structural analysis was carried out by Rietveld refinement using the x-ray diffraction results. Fe ions existed in both Fe 2+ and Fe 3+ states and occupied the Ca-(4) and Ca-(5) sites. Fe ions enhanced the degradation of β -TCP and resorption behavior onto the surface of β -TCP during the immersion test. As a result, Fe ion improves the initial cell adhesion and proliferation behavior of β -TCP.